Student’s Writing paragraph: An Error Exploration of Using Subject-Verb Agreement - Mayasari, Ichlasul Baroqah Yuni Harnita; Sari, Ulmala (research, training and philanthropy institution Natural Aceh, 2024)
This study aimed to achieve two main objectives: firstly, to identify the types of errors occurring in subject-verb agreement within students' paragraph writing, and secondly, to determine the most prevalent error type among fifth-semester students. Employing a descriptive qualitative design, the research utilized documentation and interviews as data collection methods, with documentation consisting of students' written works. The participants were fifth-semester students enrolled in the English education department. Analysis was conducted using surface strategy taxonomy. The findings revealed that students exhibited various types of subject-verb agreement errors, with misinformation being the most frequent, occurring 40 times. Consequently, the researcher recommends that lecturers provide additional explanations and examples to enhance students' understanding. Moreover, students are advised to engage in more writing practice to refine their skills. Future researchers are encouraged to expand upon this study by exploring additional phenomena related to subject-verb agreement usage. In summary, this research underscores the importance of addressing subject-verb agreement errors in academic writing. It suggests practical strategies for both educators and students to improve writing proficiency in this aspect. Moreover, it highlights avenues for further investigation to deepen our understanding of this linguistic phenomenon.